2019
DOI: 10.24818/ea/2019/51/377
|View full text |Cite
|
Sign up to set email alerts
|

Households’ Food Insecurity in the V4 Countries: Microeconometric Analysis

Abstract: Food insecurity is a salient dimension of household poverty and a crucial issue viewed on a global or within a country level. It applies not only to less-developed countries, but also to countries of the European Union. In the European conditions, it implies that people affected by this problem cannot afford enough food of sufficient quality and quantity that would allow them to stay healthy and participate in the society. This paper attempts to fill that gap in the existing literature regarding food insecurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
2
10
0
1
Order By: Relevance
“…The empirical papers usually assume that food insecurity is determined by a wide range of factors. Among them, household income is expected to be strongly positively associated with access to food [11,17,21,38,48,[58][59][60][61]. Other research papers prove that a higher share (level) of off-farm incomes [60], remittance [58,62] and social grants [63] are significant for improving food security.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The empirical papers usually assume that food insecurity is determined by a wide range of factors. Among them, household income is expected to be strongly positively associated with access to food [11,17,21,38,48,[58][59][60][61]. Other research papers prove that a higher share (level) of off-farm incomes [60], remittance [58,62] and social grants [63] are significant for improving food security.…”
Section: Introductionmentioning
confidence: 99%
“…Polish households are also investigated by Food and Agriculture Organization (FAO) [47]. The households' food insecurity in Poland was analyzed by Dudek [48]. It was indicated that in 2017, 6.3% of the Polish population could not afford a meal with meat, chicken, fish (or vegetarian equivalent) every second day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of a current state of the art using articles and studies of other authors point out at following factors within their influence on customer behaviour and preferences, namely the level of food literacy, product knowledge or purchasing power (Dudek, 2019;Erokhin, 2017;Ronto, Ball, Pendergast & Harris, 2016;Savelli, Murmura, Liberatore, Casolani & Bravi, 2019;Suchánek & Králová, 2019). Companies respond to these factors by identification of changes in established consumer behaviour in order to maintain their competitiveness that can be measured among all by financial performance indicators.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this situation can be found in the fact that prevailing amount of production, which is processed and placed on the market, is assessed as providing a lower utility value by the consumers' side. Dudek (2019) examined food insecurity in the EU, specifically in the V4. The author perceives food insecurity as a situation when people affected by this problem cannot afford enough food of sufficient quality and quantity that would allow them to stay healthy and participate in society.…”
Section: Literature Reviewmentioning
confidence: 99%